Plc-Based Starter Generator Set Automation Simulation - Mahasin, Zaenal (Sean Institute, 2023)
Maintenance of the generator set is very influential on the performance of an electric power supply. Especially in a vital institution such as a hospital. The existence of a generator is very necessary as an anticipation if the electricity supply from PLN experiences a trip. Limited time and energy are the main factors underlying the lack of generator maintenance, so generators often fail when needed. Starting from the limited time and energy, the idea emerged about the need for a software that is able to control the system automatically so that it can heat up the generator engine at any given time. Programmable logic controller (PLC) is a program that is used to operate an automatic generator set system. The command made in the form of an image that can be interpreted as a logic circuit command is called a ladder diagram. The command taken from the input signal is a switch and the output signal command is a load. The output signal in this machine is a motor which is analogous to a generator, based on the logic in the generator. When input 0001 is turned on, the timer 001 will count down 25 seconds. Once fulfilled it will start the motor, if for 3 seconds the motor does not start, it will activate the 004 team as a delay before the system starts trying to start again. If in 3 times the motor is started it still won't turn on, it will activate address 1004. Address 1004 itself is an alarm that will give a warning if the system cannot function normally and must get further checks. According to the results above, the use of software using CPM 1A can be said to have been successfully applied to simulations, but there will be significant shortcomings if it is applied for public use, due to the maximum time setting of only 16 minutes, while public use requires flexibility in the application of appropriate time settings. with the field of application. Based on the observations, it can be concluded that the initial purpose of the concept of making tools is fulfilled by the realization of a simulation. The use of PLC is very suitable to be applied to automating generator sets, but the simulation performance has not been maximized due to limited capabilities in developing PLC software timer applications. however, there will be significant drawbacks if applied for public use, due to the maximum time setting of only 16 minutes, while for public use requires flexibility in the application of time settings according to the field of application. Based on the observations, it can be concluded that the initial purpose of the concept of making tools is fulfilled by the realization of a simulation. The use of PLC is very suitable to be applied to automating generator sets, but the simulation performance has not been maximized due to limited capabilities in developing PLC software timer applications. however, there will be significant drawbacks if applied for public use, due to the maximum time setting of only 16 minutes, while for public use requires flexibility in the application of time settings according to the field of application. Based on the observations, it can be concluded that the initial purpose of the concept of making tools is fulfilled by the realization of a simulation. The use of PLC is very suitable to be applied to automating generator sets, but the simulation performance has not been maximized due to limited capabilities in developing PLC software timer applications. while the use for the public requires flexibility in the application of time settings in accordance with the field of application. Based on the observations, it can be concluded that the initial purpose of the concept of making tools is fulfilled by the realization of a simulation. The use of PLC is very suitable to be applied to automating generator sets, but the simulation performance has not been maximized due to limited capabilities in developing PLC software timer applications. while the use for the public requires flexibility in the application of time settings in accordance with the field of application. Based on the observations, it can be concluded that the initial purpose of the concept of making tools is fulfilled by the realization of a simulation. The use of PLC is very suitable to be applied to automating generator sets, but the simulation performance has not been maximized due to limited capabilities in developing PLC software timer applications.